Coronavirus disease 2019-Historical context, virology, pathogenesis, immunotherapy, and vaccine development - Sayeh Ezzikouri; Jalal Nourlil; Soumaya Benjelloun; Michinori Kohara; Kyoko Tsukiyama-Kohara (Taylor & Francis Group, 2020)
The current Coronavirus Disease 2019 (COVID-19) pandemic is causing great alarm around the world. The pathogen for COVID-19 - severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - is the seventh known coronavirus to cause pneumonia in humans. While much remains unknown about SARS-CoV-2, physicians and researchers have begun to publish relevant findings, and much evidence is available on coronaviruses previously circulating in human and animal populations. In this review, we situate COVID-19 in its context as a transboundary viral disease, and provide a comprehensive discussion focused on the discovery, spread, virology, pathogenesis, and clinical features of this disease, its causative coronaviral pathogen, and approaches to combating the disease through immunotherapies and other treatments and vaccine development. An epidemiological survey revealed a potentially large number of asymptomatic SARS-CoV-2 carriers within the population, which may hamper efforts against COVID-19. Finally, we emphasize that vaccines against SARS-CoV-2, which may be developed by 2021, will be essential for prevention of COVID-19.